Complex analysis of the national Hereditary angioedema cohort in Slovakia - Identification of 12 novel variants in SERPING1 gene - Markocsy, Adam; Hrubiskova, Katarina; Hrubisko, Martin; Freiberger, Tomas; Grombirikova, Hana; Dolesova, Lenka; Slivka Vavrova, Ludmila; Lohajova Behulova, Regina; Ondrusova, Martina; Banovcin, Peter; Vorcakova, Karolina; Jesenak, Milos (The World Allergy Organization journal, 2024)
BACKGROUND: Hereditary angioedema (HAE) is a rare autosomal dominant genetic disease characterised by acute episodes of non-pruritic skin and submucosal swelling caused by increase in vascular permeability. OBJECTIVE: Here we present the first complex analysis of the National HAE Slovakian cohort with the detection of 12 previously un-published genetic variants in SERPING1 gene. METHODS: In patients diagnosed with hereditary angioedema caused by deficiency or dysfunction of C1 inhibitor (C1-INH-HAE) based on clinical manifestation and complement measurements, SERPING1 gene was tested by DNA sequencing (Sanger sequencing/massive parallel sequencing) and/or multiplex ligation-dependent probe amplification for detection of large rearrangements. RESULTS: The Slovakian national cohort consisted of 132 living patients with confirmed HAE. We identified 51 index cases (32 families, 19 sporadic patients/112 adults, 20 children). One hundred seventeen patients had HAE caused by deficiency of C1 inhibitor (C1-INH-HAE-1) and 15 patients had HAE caused by dysfunction of C1 inhibitor (C1-INH-HAE-2). The prevalence of HAE in Slovakia has recently been calculated to 1:41 280 which is higher than average calculated prevalence. The estimated incidence was 1:1360 000. Molecular-genetic testing of the SERPING1 gene found 22 unique causal variants in 26 index cases, including 12 previously undescribed and unreported. CONCLUSION: The first complex report about epidemiology and genetics of the Slovakian national HAE cohort expands the knowledge of the C1-INH-HAE genetics. Twelve novel causal variants were present in the half of the index cases. A higher percentage of inframe variants comparing to other studies was observed. Heterozygous deletion of exon 3 found in a large C1-INH-HAE-1 family probably causes the dysregulation of the splicing isoforms balance and leads to the decrease of full-length C1-INH level.
Keywords: Genetic testing; Hereditary/epidemiology; Slovakia; Hereditary/genetics; Angioedemas; Complement C1 inhibitor protein